Use of Carob Flour in the Production of Tarhana - Herken Emine Nur (Polish Journal of Food and Nutrition Sciences)
In this study, the effect of carob flour incorporation on some physical, chemical, technological, sensory and functional properties of tarhana was investigated. Carob flour was replaced with wheat flour at 0, 5, 10, 15 and 20% levels in tarhana dough. Dietary fibre, raw fibre, ash, Ca, K, Cu, total phenolic compound contents and total antioxidant capacity of dry tarhana samples as well as the acidity values during fermentation of the wet tarhana samples increased with carob flour substitution. Samples with supplementation had lower lightness and higher Hunter a and b values. Carob flour addition decreased the viscosity and yield stress of tarhana soup samples. The results showed that carob flour addition affected all the parameters measured to various extents including sensory properties. Overall acceptability scores were most highly correlated with taste. According to the sensory analysis results, carob flour can be used successfully up to the amount of 15%.